Correlations between emotional and behavioral factors and the EDI-3 by sex - Herrod, Lisa Marie (2013)
The Eating Disorder Inventory 3 (EDI-3) is one of the most commonly used measures for assessing symptoms associated with eating disorders. Several studies have examined differences in scores on the EDI-3 constructs based on sex, however; few have examined potential behavioral and/or emotional factors that may be related to scores on the EDI-3. The purpose of this study was to consider how the domains of the Behavioral Assessment System for Children, Second Edition Self Report of Personality College Form (BASC-2 SRP COL) correlated to the constructs of the EDI-3 by sex in a population of college students. The results revealed significant Pearson’s Product-Moment Correlation coefficients in all five of the EDI-3 constructs evaluated and at least one BASC-2 SRP COL scale in females. In addition, significant correlations were observed between four of the five EDI-3 composites considered and at least one BASC-2 SRP COL scales in males. Implications for future research will be discussed within the text.